The Concept of Moral Education in Imam Al-Ghazali's Book Ayyuhal Walad and Its Relevance to Contemporary Islamic Education - Ali Tahan Uji; Muhammad Syaifullah; Jaenullah (CV. Bimbingan Belajar Assyfa, 2026)
This study aims to analyze the concept of moral education in Imam Al-Ghazali's book Ayyuhal Walad and its relevance to contemporary Islamic education. The background of this research is the moral crisis occurring among the younger generation and the tendency of Islamic education that still emphasizes cognitive aspects over character development. This research employs a qualitative approach with library research type. The primary data source is the book Ayyuhal Walad, while secondary sources include books, journals, and related scholarly articles. Data collection techniques use documentation studies, while data analysis employs content analysis. The results show that Al-Ghazali's concept of moral education encompasses three main dimensions: morals towards Allah (worship, contemplation, gratitude, repentance, tawakkul), morals towards fellow humans (teacher-student relationships, mutual assistance, advice), and morals towards oneself (application of knowledge, time utilization, learning enthusiasm). The relevance of this concept to contemporary Islamic education is evident in five aspects: integration of knowledge and morals, sincerity and diligence in learning, the concept of tawakkul, harmonious teacher-student relationships, and development of social morals. This research contributes to the development of character education that integrates classical values with modern contexts. Keywords: Moral Education, Ayyuhal Walad, Al-Ghazali, Contemporary Islamic Education